Fidel Castro Ruz in the projection of the development of the tourism in Cuba (Islas, 2021)
The objective of this article is to evaluate the projection of the development of tourism in Cuba, from the point of view of Fidel Castro Ruz. The study of the essentialities of Fidel’s ideology, even before the triumph of the Revolution, starts from a conception of integrating tourism, which also included all the regions of Cuba. It has as a basis for the promotion of tourism, not only our natural beauties, but also the history, culture and hospitality of our people, which make it until today one of the essential destinations in the Caribbean as a tourist region. It is based on the analysis of speeches, interviews with Fidel Castro and other documents of the Cuban Revolution.
Keywords: Fidel Castro’s thought; tourism; tourist development